Secondary non‐invasive prenatal screening for fetal trisomy: an effectiveness study in a public health setting. (14th September 2020) - Guy, GP; Hargrave, J; Dunn, R; Price, K; Short, J; Thilaganathan, B; ,
Abstract : Objective: To evaluate the effectiveness of secondary screening using non‐invasive prenatal testing (NIPT) in a routine NHS setting including test performance, turn‐around times (TATs) and no‐call (failure to obtain result) rates. To examine the influence of maternal and fetal characteristics on test performance. Design: Retrospective cohort. Setting: London teaching hospital. Sample: A total of 8651 pregnancies undergoing screening for fetal trisomy using NIPT provided by an NHS cell‐free DNA screening laboratory – the SAFE laboratory. Methods: Screening test evaluation and TATs. Univariate and multivariate logistic regression analysis to identify significant predictors of no‐call results and reported by low fetal fraction (<2%), very high fetal fraction (>40%) and processing failure. Main outcome measures: Test performance, TATs and no‐call rates, factors affecting no‐call results. Results: Average TAT was 4.0 days (95% CI 4.0–4.2 days). Test sensitivities for trisomies 21 and 13/18 were 98.9% (95% CI 95.9–99.9%) and 90.4% (95% CI 80.0–96.8%), respectively. The overall no‐call rate was 32/8651 (0.37%, 95% CI 0.26–0.52%). The overall risk of a no‐call result was influenced by gestational age, dichorionic twin pregnancy, history of malignancy and pregnancies affected by trisomy 13/18, but not by maternal weight or use of low‐molecular‐weight heparin. Conclusions: High‐throughput NIPT can be effectively embedded into a public health NHS setting. TATs of 4 days and no‐calls of <0.5% were well within clinically desirable tolerances. Gestational age, maternal weight, assisted reproductive techniques, use of low‐molecular‐weight heparin and past history of malignancy did not have major impacts on test no‐call rates and should not constitute reasons for withholding the option of NIPT from women. Tweetable abstract: Turn‐around times of 4 days, no‐call (test failure) rates of 0.37% and highly accurate NIPT can be successfully embedded in the NHS. Tweetable abstract: Turn‐around times of 4 days, no‐call (test failure) rates of 0.37% and highly accurate NIPT can be successfully embedded in the NHS.